Implementation of a Multidisciplinary “Code Hip” Protocol is Associated with Decreased Time to Surgery and Improved Patient Outcomes - Richard J. VanTienderen DO; Kyle Bockelman DO; Rami Khalifa MD; Michael S. Reich MD; Adam Adler MD; Mai P. Nguyen MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2021)
Background: The purpose of this study is to report outcomes data based on the implementation of a “Code Hip” protocol, a multidisciplinary approach to the care of fragility hip fracture patients focussing on medical optimization and early operative intervention. We hypothesized that implementation of this protocol would decrease time from presentation to surgical intervention and improve outcomes based on short term post-operative data. Methods: A retrospective chart review was performed on all patients aged greater than 65 years old with a fragility hip fracture from October 2015 through June 2018. In addition to demographic and patient factors, we recorded time to surgery, type of surgical interventions performed, ability to ambulate in the post-operative period, 90-day post-operative complications and overall hospital cost. Results: There were 114 patients in the pre-Code Hip cohort and 132 patients in the post-Code Hip cohort. Demographic factors were not different between the 2 cohorts. Time from presentation to surgery in the post-Code Hip cohort was shorter at 23.1 ± 16.4 hours versus 33.2 ± 27.2 hours (p < 0.001). 30.3% of patients in the post-Code Hip cohort had at least one post-operative complication compared to 42.1% in the pre-Code Hip cohort (RR = 0.72, CI = 0.51 -1.01, p = 0.05). The post-Code Hip cohort had a significantly lower rate of hospital readmission (p = 0.04), unplanned reoperation (p = 0.02), surgical site infection (p = 0.03), and sepsis (p = 0.05). Total hospital cost per patient decreased from an average of $14,079 +/- $10,305 pre-Code Hip cohort to $11,744 +/- $4,174 per patient in the post-Code Hip cohort (p = 0.02). Conclusions: Implementation of our Code Hip protocol, which invokes a multidisciplinary approach to the elderly patient with a fragility hip fracture, is associated with shorter times from presentation to surgery, increased ability to ambulate post-operatively, decreased short term post-operative complication, and decreased hospital costs. Level of Evidence: Therapeutic Level III